Uso de herramientas tecnológicas durante la pandemia covid-19 y su contribución a los docentes de las unidades educativas " Diez de agosto" y " Sagrado corazón de Jesús ". - Almeida, Mayra A. (2022)
The use of technology in the educational field has become essential, so the main objective of this comparative study was to analyze the use of technological tools during the COVID- 19 pandemic, allowing to establish their contribution in the exercise of teaching, in private Unidad Educativa “Sagrado Corazón de Jesús” Ibarra, as in a public Unidad Educativa fiscal “Diez de Agosto” Otavalo, during the school year 2021-2022, due to the fact COVID-19 pandemic generated great changes in the teaching activities by adopting a new work modality, the virtual one, as the teachers were unawere of the technological tools that should be correctly applied in their classes. The study is about a comparative type, as it relates characteristics and data between two or more variables, also relying on the inductivedeductive and analytical-synthetic method. The size of the study population corresponded to 114 teachers belonging to two high schools, to whom a survey was applied as an essential technique for collecting and comparing information. The results showed a great similarity between the two institutions regarding the use of communication tools by teachers. The programs: Zoom and Microsoft Teams, served as the main virtual communication channel; on the other hand, the applicability of the tools for digital content management was the collaborative Microsoft Office package; while, for the evaluation process a marked difference was identified, as the teachers from UE “Diez de Agosto” used Google Forms questionnaires, while those of UE “Sagrado Corazón de Jesús” evaluated using Google Classroom. The main benefits of the use of technological tools by teachers in times of pandemic was the incorporation of Information and Communication Technologies (ICTs) in curricular planning, serving as support for: interactive communication, teaching activity, typing notes, designing teaching materials, sending and receiving information. Therefore, it is concluded that the technological tools contributed positively to the teaching process in both institutions, but more training focused on improving current digital competences.